(untitled) (International Journal of Engineering and Computer Science, 2014)
A vertical axis wind turbine model having three frames with cavity vanes has been designed, fabricated and tested in a low speed wind tunnel. This type of model has a high drag coefficient when the vanes close the frame on one side while rotating with wind direction and capturing the wind efficiently. On the other side, the frame rotates in the opposite direction of the wind which opens the frame causing the wind to pass through the frame with low resistance. The model is tested in a wind tunnel with the wind speeds varying between 3 m/s and 17 m/s. The present model gives the maximum power coefficient of 0.32 at a wind speed of 8.2 m/s and tip speed ratio of 0.31 which is higher than those of the vertical axis wind turbines in the literature for the purpose of comparison. The performance of a similar prototype VAWT having a scale ratio of 10:1 is also predicted using the dimensional analysis.